Teknik Pembakaran Bata Dengan Briket Batu Bara Campuran - Muhammad Halil; Ahmadin Ahmadin; Lelawati Lelawati (MAJALAH TEKNIK SIMES, 2023)
There are many small brick-burning industries in rural areas, and especially near big cities and are industrial centers of bricks burning wood or husks. The price of this fuel continues to increase because the supply of firewood is dwindling and in the use of husks there is competition from other consumers, namely chicken farmers. Coal fuel has a good opportunity to be used in the brick industry, especially in Bengkulu. The coal combustion technique that has been introduced is a combination of coal â€“ 50% wood. In this research, the combustion technique with coal and "biocoal" is developed, namely briquettes and a mixture of coal and sawdust. For this reason, a prototype furnace has been made, namely a traditional stove with a modified combustion chamber with a capacity of 4500 bricks. Using brick raw materials from Bengkulu, whose main minerals are coaline cristobalite and albite, burning with coal and â€œbiocoalâ€ briquettes has been successfully carried out. which is better achieved energy efficiency of 70% as a cheaper alternative, it has been tried burning with a mixture of coal and wood chips with a ratio of 7: 3 produces an energy efficiency of about 58% with the same raw brick material burning efficiency with a combination of coal-wood in Traditional stoves average 36% with a ratio of coal and wood of 1:8.